On the use of Aluminium as a plasmonic material in polarization rotators based on a hybrid plasmonic waveguide - Khaleel, Farooq Abdulghafoor; Tawfeeq, Shelan Khasro (Iraqi Journal of Laser, 2022)
: The Aluminium (Al) material emerged as a plasmonic material in the wavelength ranges from the ultraviolet to the visible bands in different on-chip plasmonic applications. In this paper, we demonstrate the effect of using Al on the electromagnetic (EM) field distribution of a compact hybrid plasmonic waveguide (HPW) acting as a polarization rotator. We compare the performance of Al with other familiar metals that are widely used as plasmonic materials, which are Silver (Ag) and Gold (Au). Furthermore, we study the effect of reducing the geometrical dimensions of the used materials on the EM field distributions inside the HPW and, consequently, on the efficiency of the polarization rotation. We perform the study based on the Finite Element Method (FEM) using COMSOL software at an operation wavelength of 700 nm. This paper verifies that the Al could be used as an efficient plasmonic material in integrated single-photon sources for quantum key distribution systems.